Optimalisasi Hasil dan Motivasi Belajar Fisika melalui Model Discovery Learning pada Materi Suhu dan Kalor - Gerosa Deity Kurniati; Isabel Coryunitha Panis; Egidius Dewa (U-Teach: Journal Education of Young Physics Teacher, 2024)
Low physics learning outcomes and motivation among students are problems that require effective solutions. This study aims to measure the improvement of physics learning outcomes and motivation through the discovery learning (DL) model. This research was conducted at Santa Familia Catholic Junior High School in the academic year 2023/2024 with a sample of 34 seventh-grade students selected by purposive sampling. Research instruments include a learning implementation plan (RPP), teaching materials, student worksheets (LKPD), learning outcomes tests and learning motivation questionnaires. Data analysis using descriptive analysis and N-Gain test using SPSS. The results showed an increase in average learning outcomes from 45.90 (poor category) to 85.00 (very good category), as well as an increase in learning motivation from 57.88% (moderate category) to 79.03% (high category). The N-Gain test revealed an increase in learning outcomes of 0.72 and learning motivation of 0.51. Thus, the Discovery Learning model proved to be effective in improving physics learning outcomes and motivation in the material of temperature and heat